An evaluation of the variable‐resolution CESM for modeling California's climate. (18th March 2016) - Huang, Xingying; Rhoades, Alan M.; Ullrich, Paul A.; Zarzycki, Colin M.
Abstract: In this paper, the recently developed variable‐resolution option within the Community Earth System Model (VR‐CESM) is assessed for long‐term regional climate modeling of California at 0.25° (∼28 km) and 0.125° (∼14 km) horizontal resolutions. The mean climatology of near‐surface temperature and precipitation is analyzed and contrasted with reanalysis, gridded observational data sets, and a traditional regional climate model (RCM)—the Weather Research and Forecasting (WRF) model. Statistical metrics for model evaluation and tests for differential significance have been extensively applied. With only prescribed sea surface temperatures, VR‐CESM tended to produce a warmer summer (by about 1–3°C) and overestimated overall winter precipitation (about 25%–35%) compared to reference data sets. Increasing resolution from 0.25° to 0.125° did not produce a statistically significant improvement in the model results. By comparison, the analogous WRF climatology (constrained laterally and at the sea surface by ERA‐Interim reanalysis) was ∼1–3°C colder than the reference data sets, underestimated precipitation by ∼20%–30% at 27 km resolution, and overestimated precipitation by ∼65–85% at 9 km. Overall, VR‐CESM produced comparable statistical biases to WRF in key climatological quantities. This assessment highlights the value of variable‐resolution global climate models (VRGCMs) in capturing fine‐scale atmospheric processes, projecting future regional climate, and addressing the computational expense of uniform‐resolution global climate models. Key Points: Variable‐resolution GCMs provide a means to access regional scales in a global modeling system VR‐CESM, a variable‐resolution GCM, is able to accurately model regional climate over California For temperature and precipitation, VR‐CESM demonstrates competitive solution quality to a RCM (WRF)